Penerapan Model Problem Based Learning Dalam Meningkatkan Hasil Belajar Peserta Didik Kelas IV UPTD SD Negeri 09 Pintuai - Yulita, Herni (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
Based on the assessment results conducted by the author during the 2023/2024 academic year for the fourth-grade students of UPTD SDN 09 Pintuai, it shows that student activity and learning outcomes are still suboptimal. The purpose of this study is to determine how the application of the Problem-Based Learning (PBL) model can improve student learning outcomes in the subject of Islamic Religious Education (PAI) and to examine the extent to which the PBL model can enhance learning outcomes in the topic of the noble example of Asmaul Husna in PAI. The method used is Classroom Action Research. The results from Cycle I and II show significant improvement in student activity and learning outcomes. All students achieved mastery in learning, with an average score higher than in Cycle I. The strategy applied successfully increased student attention and participation. The PBL model proved to be effective, with better planning and actions. Therefore, the study can be concluded as successful.